Skill Development in India : The Vocational Education and Training System - World Bank (Washington, DC, 2014)
This paper stresses that despite the fact that India is a fast developing economy difficulties have led the Government to conclude that far more needs to be done to engender more employment opportunities for the majority of Indians, to enable them to participate in the benefits of growth and to contribute to that growth. To do this they must have education and training that equips them for the labor market. One of the sources of the skilled workforce is the vocational education and training system. However, the government realizes that the system is not being able to appropriately respond to the needs of the labor market. A key issue, then, is what reforms/interventions are needed to improve the effectiveness of the system. Answering that question is far from easy and this paper attempts to provide some options for doing so. On the one hand India faces the future with its changing realities; on the other hand it must deal with the nature of its established traditions and structures. This paper has laid out some key reforms that must be undertaken in different areas to make the vocational education and vocational training systems more responsive to the needs of the labor market. The reform agenda is fairly comprehensive and all the reforms cannot be implemented immediately. Given this, the paper has laid out some of the critical reforms that need to be undertaken in the short-run (first phase) followed by others that can be undertaken over a period of 2-3 years. The first phase focuses on reforms aimed at improving the quality and labor market relevance of the existing system, while the medium-term agenda also includes moving forward on mobilizing additional resources for the system, especially once the quality has improved. However the background work needed to undertake reforms in the medium-term should also commence immediately. These reforms should be treated as a package. If only some are instituted, while others are not, it is unlikely that the objective of developing a truly demand-responsive system will be effectively met.